IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 2 TAHUN 2016 TENTANG KARTU IDENTITAS ANAK DI KANTOR DINAS KEPENDUDUKAN CATATAN SIPIL KABUPATEN BANYUASIN - Haryani, Deffi (Jurnal Ilmiah Administrasi Dan Sosial, 2023)
This study aims to analyze how the implementation of the Minister of Home Affairs RegulationNumber 2 of2016  concerning  Child Identity  Cards at the Office of  the Civil Registry Office of Banyu asin Regency (CaseStudy  ofBanyuasin  IIIDistrict,  BanyuasinRegency)  This  study uses  qualitative research  methods,  data  collection  techniques  using  observation,  interviews,documentation  and  literature study. The findings of this study at the Banyuasin Sub-district Office incarrying out six implementation indicators,   namely   policy   standards   and   targets,   Resources,   Inter-organizational   communication, Characteristics of implementing agents, Economic, social and politicalenvironment and the attitude of the implementers are good enough so that the quality of service isincludedin agood category. in implementation. Based  on  the results  of  research  and  discussion  of  the  findings  of  researchers  in  the  field  regarding theimplementation   of   the   Minister   of   Home   Affairs   Regulation   Number   2   of   2016   concerning Child Identity Cards at the Office of Population and Civil Registration of Banyuasin Regency (CaseStudyofBanyuasin District III, Banyuasin Regency) has not been fully implemented properly because there isstill a lack of socialization- direct socialization in a persuasive manner to the community so that thereare still people who do  not  understand  the  use  and  importance  of  this  child  identity card  and  have  not achieved the target in making child identity cardsin Banyuasin III District. Keywords: Implementation, Child Identity Card